1996
DOI: 10.1524/ract.1996.75.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Uranium(VI) in Nitric Acid Solution with Supercritical Carbon Dioxide Fluid Containing Tributylphosphate

Abstract: Extraction behaviors of U(VI) and selected fission product elements from HN0 3 solution into a supercritical C0 2 fluid containing tributylphosphate (TBP) were studied under equilibrium and dynamic extraction conditions. Uranium(VI) was found to be extracted in the supercritical C0 2 phase as a form of U0 2 (N0 3 ) 2 (TBP) 2 with a distribution ratio of, e.g., 2.2±0.3 for the extraction of 2 X10" 4 to 2 X 10" 2 M U(VI) from 3 M HN0 3 into supercritical C0 2 -0.3 M TBP mixture at 60°C and 15 MPa. The distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 10 publications
7
61
0
Order By: Relevance
“…The parameters obtained are given in Table 1. The product of ha and D/a 2 can be shown to be equal to K c F/3V and by using the experimental flow rates and sample volumes (6 ml and 1.4 ml per min for the present data and 5 ml and 1.1 ml per min, 12) respectively) the values of the partition coefficient, K c , can be obtained and these are shown in the final column of the table. Bearing in mind that the model is limited, the relative values of the results can be discussed.…”
Section: Adaptation To the Extraction Of Solutions Of Uranium Ionsmentioning
confidence: 78%
See 1 more Smart Citation
“…The parameters obtained are given in Table 1. The product of ha and D/a 2 can be shown to be equal to K c F/3V and by using the experimental flow rates and sample volumes (6 ml and 1.4 ml per min for the present data and 5 ml and 1.1 ml per min, 12) respectively) the values of the partition coefficient, K c , can be obtained and these are shown in the final column of the table. Bearing in mind that the model is limited, the relative values of the results can be discussed.…”
Section: Adaptation To the Extraction Of Solutions Of Uranium Ionsmentioning
confidence: 78%
“…12) Since the modelling indicates the process is mainly controlled by diffusion in the aqueous phase, it is then further implied that the better performance of the carbon dioxide system is due to better contact between the fluids, perhaps due to smaller bubble sizes. A possible explanation is that, because of the larger density difference with the aqueous phase (carbon dioxide at 150 bar and 60…”
Section: Model Predictions Of Optimum Flow Ratementioning
confidence: 99%
“…The species UO 2 (NO 3 ) 2 (TBP) 2 was confirmed as the extracted species in the supercritical CO 2 extraction system 13) identically to the species in the traditional solvent extraction system of U(VI) from nitric acid solution into organic solvent containing TBP.…”
Section: Resultsmentioning
confidence: 72%
“…Several studies have demonstrated that MA(III), Ln(III), and uranyl ion (U(VI)) can be extracted from solid or liquid materials to scCO 2 as soluble complexes with chelating ligands such as organophosphorus compounds and b-diketones [7][8][9][10][11][12]. The solubility of various metal complexes including U(VI) in scCO 2 has been investigated, and the results have indicated that fluorination of coordinated ligands drastically enhances the solubility of metal complexes by several orders of magnitude compared with non-fluorinated analogues [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%